Trypanosoma cruzi Induces B Cells That Regulate the CD4+ T Cell Response - Somoza, Martín; Bertelli, Adriano; Pratto, Cecilia A.; Verdun, Ramiro E.; Campetella, Oscar; Mucci, Juan (Frontiers in Cellular and Infection Microbiology, 2022)
Trypanosoma cruzi infection induces a polyclonal B cell proliferative response characterized by maturation to plasma cells, excessive generation of germinal centers, and secretion of parasite-unrelated antibodies. Although traditionally reduced to the humoral response, several infectious and non-infectious models revealed that B lymphocytes could regulate and play crucial roles in cellular responses. Here, we analyze the trypomastigote-induced effect on B cells, their effects on CD4+ T cells, and their correlation with in vivo findings. The trypomastigotes were able to induce the proliferation and the production of IL-10 or IL-6 of naïve B cells in co-culture experiments. Also, we found that IL-10-producing B220lo cells were elicited in vivo. We also found up-regulated expression of FasL and PD-L1, proteins involved in apoptosis induction and inhibition of TCR signaling, and of BAFF and APRIL mRNAs, two B-cell growth factors. Interestingly, it was observed that IL-21, which plays a critical role in regulatory B cell differentiation, was significantly increased in B220+/IL-21+ in in vivo infections. This is striking since the secretion of IL-21 is associated with T helper follicular cells. Furthermore, trypomastigote-stimulated B-cell conditioned medium dramatically reduced the proliferation and increased the apoptotic rate on CD3/CD28 activated CD4+ T cells, suggesting the development of effective regulatory B cells. In this condition, CD4+ T cells showed a marked decrease in proliferation and viability with marginal IL-2 or IFNγ secretion, which is counterproductive with an efficient immune response against T. cruzi. Altogether, our results show that B lymphocytes stimulated with trypomastigotes adopt a particular phenotype that exerts a strong regulation of this T cell compartment by inducing apoptosis, arresting cell division, and affecting the developing of a proinflammatory response.